The Perfectionist Call of Intelligibility: Secondary English, Creative Writing, and Moral Education - Belas, Oliver (Philosophical Inquiry in Education, 2016)
This article puts forward moral-philosophical arguments for re-building and re-thinking secondary-level (high-school equivalent) English studies around creative writing practices. I take it that when educators and policy makers talk about such entities as the "well-rounded learner," what we have, or should have, in mind is moral agents whose capacities for moral dialogue, judgement, and discourse are increased as a result of their formal educational experiences. In its current form, secondary English is built mainly, though not exclusively, around reading assessment; around, that is, demonstration of students' "comprehension" of texts. There is little or no sense that the tradition and practice of literary criticism upon which this type of assessment is based is a writerly tradition. By making writing practices central to what it is to do English in the secondary classroom, I argue that we stand a better chance at helping students develop their capacities for self-expression, for articulating their developing webs of belief and for scrutinizing those webs of belief. I thus wish to think about English and Creative Writing Studies in light of Cavell’s moral perfectionism, and to conceive of it as an arts-practical subject and a mode by which one might, in Baldacchino’s sense, undergo a process of "unlearning." My arguments are tailored to the English educational context.